153k views
4 votes
Drag the tiles to the correct boxes to complete the pairs.

Using the properties of integer exponents, match each expression with the correct equivalent expression.

Drag the tiles to the correct boxes to complete the pairs. Using the properties of-example-1

2 Answers

3 votes

Answer:

The answer is 1-2 2-4 3-4 and 4-3

Explanation:

User Shesek
by
6.2k points
3 votes

Answer:

1.
(-2^2)^(-6) ÷
(2^(-5))^(-4) \implies 2^(-32)

2.
2^4 . (2^2)^(-2) \implies 1

3.
(-2^(-4)).(2^2)^0 \implies -2^8

4.
(2^2).(2^3)^(-3) \implies 2^(-5)

Explanation:

1.
(-2^2)^(-6) ÷
(2^(-5))^(-4) :


= \frac{ ( - 2 ^ 2 ) ^ { - 6 } } { ( 2 ^ { - 5 } ) ^ { - 4 } } = (2^(-12))/(2^(20)) = 2^(-12-20)=2^(-32)

2.
2 ^ 4 . ( 2 ^ 2 ) ^ { - 2 } :


= 2^4 * (1)/(2^4) = 1

3.
(-2^(-4)).(2^2)^0 :


= (-2^4)^2 * 1 = -2^8

4.
(2^2).(2^3)^(-3) :


= 2^4 * (1)/(2^9) =(1)/(2^5) =2^(-5)

User Sivanand Kheti
by
5.3k points